Twin-to-twin transfusion syndrome known methods of treatment - Sosna, Monika; Misiło, Adriana; Mordoń, Krzysztof (Journal of Education, Health and Sport, 2023)
Pregnancy is a state of emergency for most women and is usually a great happiness. Twin pregnancy should bring double happiness. Unfortunately, it often means more problems, more research, more worries. TTTS is a twin-to-twin transfusion syndrome that carries many complications.It occurs in 5-25% of monochorionic twin pregnancies. The severity of the disease is determined using the Quintero scale. The methods of treatment include fetoscopic laser photocoagulation, expectant management, amnioreduction, termination of pregnancy, usually when the fetal lungs are mature. The prognosis depends on many factors, including the type of vascular anastomoses. There are two types of TTTS: acute and chronic.